Constitutional rationalisation of legislation dealing with traditional justice system - Ngema, Phumelele O P (2014)
My thesis addresses the question of whether an imposed traditional justice system operating through traditional courts is still relevant in South Africa. I interrogate whether traditional courts are necessary in a constitutional democracy outside of the existing western type courts system. The Constitution, in terms of chapter 12, recognises traditional leaders and enjoins government to enact national legislation that provides for the role of traditional leadership at a local level. As a unitary democratic state with diverse cultures, the Constitution also acknowledges and grounds diversity which could be interpreted as permitting legal pluralism. I argue that the Constitution envisages recognition and application of the indigenous system within the existing courts of law and subject to the Constitution. Traditional leaders must be recognised in line with the injunction that customary law must be developed and applied by courts. Any other different construction on how traditional courts may be rationalised promotes the interest of traditional leaders and creates an unstable pluralist legal system enabling inequality and discrimination contrary to constitutional imperatives